Allamanda bolivinensis Bolivian Allamanda - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS, 2018)
This document provides a detailed overview of the Bolivian Allamanda (Allamanda bolivinensis), an evergreen vine known for its vivid white, trumpet-shaped flowers with deep yellow throats. It describes the plant’s characteristics, including its rapid growth rate, spreading habit, and adaptability to various soil types. The document highlights the plant’s uses in landscaping, such as covering trellises, arbors, and retaining walls, and its suitability for hanging baskets. It also notes the plant’s high drought tolerance and minimal pest issues, making it an attractive option for gardeners in frost-free locations. Additionally, the document discusses the plant’s maintenance requirements, including the need for full sun and regular pinching to manage its growth. Original publication date October 1999.